A modified approach for the site-selective direct C-6 arylation of benzylated uracil. Issue 52 (26th December 2019) - Savitha, Bhaskaran; Reddy, Eeda Koti; Kumar, C.S. Ananda; Karuvalam, Ranjith P.; Padusha, M. Syed Ali; Bakulev, Vasiliy A.; Narasimhamurthy, Kereyagalahally H.; Sajith, Ayyiliath M.; Joy, Muthipeedika Nibin
Graphical abstract: Highlights: An efficient methodology for the regioselective C-6 arylation of protected uracil has been achieved. The adopted methodology is facile and compatible with aryl bromides, iodides and even boronic acids. The selective deprotection strategy to access the uracil analogues with free NH has been achieved. Abstract: An efficient methodology is reported for the regioselective C-6 arylation of protected uracil via the palladium catalyzed CH functionalization of 1-(4-methoxybenzyl)-3-methylpyrimidine-2, 4( 1H, 3H )-dione with (hetero)aryl halides and boronic acids. Utilization of the Pd(OAc)2 /Xantphos catalytic system with a stoichiometric amount of CuI and DBU as the base was vital for the success of this protocol. The methodology is facile and compatible with aryl bromides, iodides and boronic acids and hence affords broad substrate scope and diversity.